From theories of human behavior to rules of rational choice: Tracing a normative turn at the cowles commission, 1943-1954 - Catherine Herfeld (Duke University, Center for the History of Political Economy (CHOPE), 2017)
This article traces a normative turn between the middle of the 1940s and the early 1950s reflected in the reformulation, interpretation, and use of rational choice theories at the Cowles Commission for Research in Economics. This turn is paralleled by a transition from Jacob Marschak's to Tjalling Koopmans' research program. While rational choice theories initially raised high hopes that they would serve as empirical accounts to inform testable hypotheses about economic regularities, they became increasingly modified and interpreted as normative approaches offering behavioral recommendations for individual agents, organizations, government, or teams. The predefined elements constitutive of these accounts, inspired by simple rules of logic were now meant to represent the basic demands of rationality, while theories of rational decision-making specified rules of conduct that were meant to shape rather than explain behavior.
Keywords: B00; B2; B3; B4; 330; history of rational choice theory; Cowles Commission; normative turn